Perfluorooctanoic acid induces mitochondrial dysfunction in MC3T3-E1 osteoblast cells. Issue 3 (23rd February 2017) - Choi, Eun Mi; Suh, Kwang Sik; Rhee, Sang Youl; Oh, Seungjoon; Woo, Jeong-Taek; Kim, Sung Woon; Kim, Young Seol; Pak, Youngmi Kim; Chon, Suk
ABSTRACT: Perfluorooctanoic acid (PFOA), a stable organic perfluorinated compound, is an emerging persistent organic pollutant, found widely in human and wildlife populations. Recent evidence suggests that exposure to environmental toxicants can be associated with higher risks of osteoporosis and fractures. We studied the cellular toxicology of PFOA in MC3T3-E1osteoblast cells. To examine the effect of PFOA, we measured cell viability, reactive oxygen species (ROS), mitochondrial superoxide, and mitochondrial parameters including adenosine triphosphate (ATP) level, mitochondrial membrane potential (MMP), cardiolipin content, and cytochrome c release in MC3T3-E1 cells. Incubating MC3T3-E1 cells in different concentrations of PFOA for 48 h resulted in a concentration-dependent decrease in cell viability and significant inductions of ROS and mitochondrial superoxide. Moreover, PFOA induced MMP collapse, cardiolipin peroxidation, cytochrome c release, and decreased ATP levels, which in turn induced apoptosis or necrosis. When osteoblast differentiation markers were assessed, PFOA treatment caused a significant reduction in alkaline phosphatase activity, collagen synthesis, and mineralization in the cells. In summary, we found an ROS- and mitochondria-mediated pathway for the induction of cell damage by PFOA in MC3T3-E1 cells. Together, our results indicate that mitochondrial toxicity could be a plausible mechanism for the toxic effects of PFOA on osteoblast function.